2020
DOI: 10.1002/adhm.202001108
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolytic Carbon Nanograss Enhances Neurogenesis and Dopaminergic Differentiation of Human Midbrain Neural Stem Cells

Abstract: Advancements in research on the interaction of human neural stem cells (hNSCs) with nanotopographies and biomaterials are enhancing the ability to influence cell migration, proliferation, gene expression, and tailored differentiation toward desired phenotypes. Here, the fabrication of pyrolytic carbon nanograss (CNG) nanotopographies is reported and demonstrated that these can be employed as cell substrates boosting hNSCs differentiation into dopaminergic neurons (DAn), a long-time pursued goal in regenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Scanning electron microscope (SEM) imaging of the generated scaffold and subsequent organoid formation showed that silk, templated by air bubbles, polymerizes into flat microfibers with thickness of ~1 µm and composed of defined nanofibrils (Figure 1G). Notably, nano-topography could play an important role by facilitating and enhancing cell adhesion and neuronal growth even on cell-inert substrates (Asif et al, 2020). SEM images further show that both neuronal progenitors interact directly with the silk surface and successfully attached along the length of the silk microfibers in the engineered organoids (Figure 1H) while differentiating into mature neurons with projections extending along the silk scaffold (Figure 1I, Supplementary Figure S1A,B).…”
Section: Generation Of Silk Cerebral Organoidsmentioning
confidence: 95%
“…Scanning electron microscope (SEM) imaging of the generated scaffold and subsequent organoid formation showed that silk, templated by air bubbles, polymerizes into flat microfibers with thickness of ~1 µm and composed of defined nanofibrils (Figure 1G). Notably, nano-topography could play an important role by facilitating and enhancing cell adhesion and neuronal growth even on cell-inert substrates (Asif et al, 2020). SEM images further show that both neuronal progenitors interact directly with the silk surface and successfully attached along the length of the silk microfibers in the engineered organoids (Figure 1H) while differentiating into mature neurons with projections extending along the silk scaffold (Figure 1I, Supplementary Figure S1A,B).…”
Section: Generation Of Silk Cerebral Organoidsmentioning
confidence: 95%
“…[ 4–9 ] In this framework, conductive substrates made by, or enriched with, carbon‐based nanomaterials (as carbon nanotubes [CNT] or graphene) have proved pivotal in interfacing nerve cells and studying their behavior. [ 10–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] In this framework, conductive substrates made by, or enriched with, carbon-based nanomaterials (as carbon nanotubes [CNT] or graphene) have proved pivotal in interfacing nerve cells and studying their behavior. [10][11][12] In particular, for neuronal or progenitor cell cultures, NP patterned substrates have been designed to significantly influence proliferation and guidance, neural differentiation, outgrowth, and development. [13,14] In the field of neuroscience, vertical nanowires or NPs have been shown to support the formation of axons in hippocampal neurons, and that of functional neuronal networks.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches for the microfabrication of biocompatible carbon microelectrodes have been investigated, such as inkjet printing [17], UV lithography [18,19], plasma etch-ing [20,21], and UV embossing [22]. Most of these strategies are based on the so-called carbon MEMS (CMEMS) process [23].…”
Section: Introductionmentioning
confidence: 99%